2021
DOI: 10.1038/s41467-021-23761-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing vaccine allocation for COVID-19 vaccines shows the potential role of single-dose vaccination

Abstract: Most COVID-19 vaccines require two doses, however with limited vaccine supply, policymakers are considering single-dose vaccination as an alternative strategy. Using a mathematical model combined with optimization algorithms, we determined optimal allocation strategies with one and two doses of vaccine under various degrees of viral transmission. Under low transmission, we show that the optimal allocation of vaccine vitally depends on the single-dose efficacy. With high single-dose efficacy, single-dose vaccin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
108
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 38 publications
14
108
0
1
Order By: Relevance
“…The optimal order of prioritization will depend upon the measure being optimized (i.e. protecting essential societal functions or directly minimizing health harms, such as cases, hospitalizations or deaths, or some combination of these) [10][11][12]. In the UK, vaccination policy advice is provided by the Joint Committee on Vaccination and Immunization (JCVI).…”
Section: Introductionmentioning
confidence: 99%
“…The optimal order of prioritization will depend upon the measure being optimized (i.e. protecting essential societal functions or directly minimizing health harms, such as cases, hospitalizations or deaths, or some combination of these) [10][11][12]. In the UK, vaccination policy advice is provided by the Joint Committee on Vaccination and Immunization (JCVI).…”
Section: Introductionmentioning
confidence: 99%
“…The baseline values of vaccine efficacy used in the model are listed in Table 1 . The overall vaccine effectiveness against disease (denoted by VE ) was modeled as a function of the risk of infection and risk of symptomatic disease, conditional to infection [ 27 ]. Specifically, the vaccine effectiveness ( ) against strain j ( j = 1 for wild-type and j = 2 for SARS-CoV-2 variant) among age group k is represented as where represents vaccine efficacy against infection and represents the efficacy against symptomatic disease, conditional to infection.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the study explains how memory B cells develop properly following the administration of mRNA vaccines, supporting the idea that further enhancement of antibody production is stimulated by a second dose of vaccine given up to 6 months after the first ( 14 ). Similarly, recent epidemiological modeling studies on SARS-CoV-2 showed the effectiveness of single dose vaccination strategy in containing the pandemic more rapidly ( 15 ). The debate is still ongoing among scientists and public health policymakers at both the national and international level ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 91%